Implications Of Counseling Guidance On Teenager’s Hanging Out Lifestyles - Hamidah, Aisyah Ummu; Rafiola, Ryan Hidayat; Ayu, Siska Putri (Guidance : Jurnal Bimbingan dan Konseling, 2024)
The aim of this mini research is to find out interaction patterns and interactional dynamics, adolescent lifestyles and the implications of guidance services for high school students. This research method uses symbolic interactionism, sampling informants using purposive sampling and collaborating with snowball. The research results showed that the group of high school teenagers that the researchers observed had a habit of hanging out in this group not as a place to show off on social media, indeed some uploaded it to social media but not to show their orders or the appearance of the clothes they were wearing. Groups also make their activities meaningful by exchanging ideas and the latest information. The final result is that this group has great potential in supporting guidance and counseling services, group guidance which is very similar to problem solving techniques and group counseling.